Prognostic impact of extracapsular lymph node involvement after neoadjuvant therapy and oesophagectomy. Issue 12 (3rd October 2016) - Lagarde, S M; Navidi, M; Gisbertz, S S; van Laarhoven, H W M; Sumpter, K; Meijer, S L; Disep, B; Immanuel, A; Griffin, S M; van Berge Henegouwen, M I
Abstract: Background: The significance of extracapsular lymph node involvement (LNI) is unclear in patients with oesophageal cancer who have undergone neoadjuvant treatment followed by oesophagectomy. The aim of this study was to assess the incidence and prognostic significance of extracapsular LNI in a large multicentre series of consecutive patients with oesophageal cancer treated by neoadjuvant chemotherapy or chemoradiotherapy and surgery. Methods: Data from a consecutive series of patients treated at two European centres were analysed. All patients with squamous cell carcinoma or adenocarcinoma of the oesophagus or gastro-oesophageal junction, who received neoadjuvant chemotherapy or chemoradiation followed by transthoracic oesophagectomy and two-field lymphadenectomy with curative intent, were included. Results: Between January 2000 and September 2013, 704 patients underwent oesophagectomy after neoadjuvant therapy. A median of 28 (range 5–77) nodes per patient was recovered. Some 347 patients (49·3 per cent) had no LNI (ypN0). Of the remaining 357 patients (50·7 per cent) with LNI (ypN1–3), extracapsular LNI was found in 190 (53·2 per cent). Five-year overall survival rates were 62·7 per cent for patients with N0 disease, 44·9 per cent for patients without extracapsular spread and 14·0 per cent where extracapsular LNI was identified ( P < 0·001). Multivariable analyses demonstrated the presence of extracapsular LNI as an independent prognostic factor. Conclusion: The presence of extracapsular LNI after neoadjuvant therapy carries a poor prognosis. Abstract : Bad news